2014
DOI: 10.1111/ppl.12268
|View full text |Cite
|
Sign up to set email alerts
|

Thylakoid membrane oxidoreductase LTO1/AtVKOR is involved in ABA‐mediated response to osmotic stress in Arabidopsis

Abstract: Arabidopsis lumen thiol oxidoreductase 1 (LTO1) - the At4g35760 gene product - was previously found to be related to reactive oxygen species (ROS) accumulation. Here, we show that ROS accumulated in a mutant Arabidopsis line (lto1-2, mutant of LTO1/AtVKOR) under osmotic stress at a higher level than that observed in wild-type and transgenic complemented plants of the lto1-2 mutant (lto1-2C, transgenic complemented plants of lto1-2). Because ROS accumulation in osmotic stress is triggered by abscisic acid (ABA)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…S1). The ANN1 gene is a well-established marker of the WD response in Arabidopsis (Konopka-Postupolska et al, 2009;Lu et al, 2015), and its expression was persistently elevated in Col-0 plants grown under conditions similar to those Table II. Partitioning of phenotypic variance among accessions subjected to three watering conditions…”
Section: Natural Variation Of Responses Among Arabidopsis Accessions mentioning
confidence: 99%
See 1 more Smart Citation
“…S1). The ANN1 gene is a well-established marker of the WD response in Arabidopsis (Konopka-Postupolska et al, 2009;Lu et al, 2015), and its expression was persistently elevated in Col-0 plants grown under conditions similar to those Table II. Partitioning of phenotypic variance among accessions subjected to three watering conditions…”
Section: Natural Variation Of Responses Among Arabidopsis Accessions mentioning
confidence: 99%
“…The main selection criterion was the expression level of the drought-response marker ANN1, which was analyzed and quantified during a preliminary experiment (KonopkaPostupolska et al, 2009;Lu et al, 2015). Seedlings of 94 accessions derived from three different collections (McKhann, Weigel, and Nordborg) were screened during that preliminary experiment and provided data on the extremely high and low levels of ANN1 mRNA.…”
Section: Plant Materialsmentioning
confidence: 99%
“…It contains a transit peptide at the N‐terminus, which targets the protein to the thylakoid (Feng et al ., ). Loss of LTO1 activity has been associated with a severe depletion of the structural subunits of photosystem II (like D1 protein), which consequently led to a limitation in electron flow from PSII and an increased accumulation of reactive oxygen species and thus severe photoautotrophic growth defect and photoinhibition (Karamoko et al ., ; Lu et al ., , ; Yu et al ., ; Du et al ., ).…”
Section: Disulfide Bond Formation On Luminal Proteins In Thylakoidsmentioning
confidence: 99%
“…The results indicated that down‐ and up‐regulation of Sl VKOR in vivo changed the activities of antioxidant enzymes and resulted in differential accumulation of ROS. Our recent study also showed that the involvement of At VKOR to osmotic stress was related to abscisic acid synthesis in Arabidopsis (Lu et al ). In resistance to osmotic stress, Sl VKOR may play an important role in facilitating cross‐talk between ROS homeostasis and the abscisic acid signal pathway.…”
Section: Discussionmentioning
confidence: 76%
“…Deficiency of AtVKOR results in a photosynthetic defect and the increased accumulation of ROS even under normal growth condition (Lu et al 2013, Yu et al 2014. Recently, it is demonstrated that AtVKOR is involved in an abscisic acid (ABA)-mediated response to osmotic stress in Arabidopsis (Lu et al 2015).…”
Section: Introductionmentioning
confidence: 99%